2014
DOI: 10.1152/ajpregu.00177.2014
|View full text |Cite
|
Sign up to set email alerts
|

The ins and outs of angiotensin processing within the kidney

Abstract: The kidney is a key target organ for bioactive components of the renin-angiotensin system (RAS); however, various renal cells such as the tubular epithelium contain an intrinsic RAS. The renal RAS can be functionally divided into ANG II-AT1 receptor and ANG-(1-7)-AT7/Mas receptor arms that functionally oppose one another. The current review considers both extracellular and intracellular pathways that potentially govern the formation and metabolism of angiotensin peptides within the renal proximal tubules.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 15 publications
(46 reference statements)
0
15
0
Order By: Relevance
“…Peptidases are generally distinguished from proteases by their preference to hydrolyze peptides of 5 to 30 amino acids in length. In contrast to renin, the peptidases associated with the RAS do not exhibit exclusive specificity for angiotensins, although certain enzymes may exhibit preferential kinetics such as ACE2 for ANG II (112,145). An extensive peptidase class is the metalloenzymes [ACE, ACE2, neprilysin (Nep), aminopeptidase A] that require divalent cations for activity; thus the assessment of activity in the circulation is performed in serum in the absence of strong chelating agents such as EDTA or phenanthroline.…”
Section: Ras Protein Componentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Peptidases are generally distinguished from proteases by their preference to hydrolyze peptides of 5 to 30 amino acids in length. In contrast to renin, the peptidases associated with the RAS do not exhibit exclusive specificity for angiotensins, although certain enzymes may exhibit preferential kinetics such as ACE2 for ANG II (112,145). An extensive peptidase class is the metalloenzymes [ACE, ACE2, neprilysin (Nep), aminopeptidase A] that require divalent cations for activity; thus the assessment of activity in the circulation is performed in serum in the absence of strong chelating agents such as EDTA or phenanthroline.…”
Section: Ras Protein Componentsmentioning
confidence: 99%
“…The peptidase is a membranebound and glycosylated protein (120 -180 kDa); however, soluble forms of the enzyme are present in the circulation, cerebrospinal fluid, lymph, and urine (15). ACE plays a key role in the formation of ANG II, but the peptidase metabolizes other peptides including bradykinin, substance P, acetyl-SerAsp-Lys-Pro, and ANG-(1-7) (16,145). ACE activity is typically measured by small peptide substrates such as hippurylHis-Leu or furylacrylol-Phe-Ala-Gly-Gly in a buffer containing chloride (10 -200 mM) and zinc (1-100 M) for optimal peptidase activity (24,122).…”
Section: Ras Protein Componentsmentioning
confidence: 99%
See 1 more Smart Citation
“…We demonstrated a role for ACE in the metabolism of Ang-(1-7), but there are other potential pathways that may regulate endogenous levels of the peptide [95]. Marshall and colleagues reported that ACE and a second peptidase activity in the sheep cerebrospinal fluid degraded Ang-(1-7) [95][96][97].…”
Section: Dipeptidyl Peptidasementioning
confidence: 75%
“…Marshall and colleagues reported that ACE and a second peptidase activity in the sheep cerebrospinal fluid degraded Ang-(1-7) [95][96][97]. Interestingly, the non-ACE-degrading activity accounted for a greater contribution of metabolism than ACE [96].…”
Section: Dipeptidyl Peptidasementioning
confidence: 99%